Pengaruh Kehadiran Minimarket Terhadap Pendapatan Kios Kecil di Kelurahan Tataaran II Kecamatan Tondano Selatan - Pero Resi Sihombing; Fonny Rewah; Xaverius Erick Lobja (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
The purpose of this study was to determine the effect of minimarkets on the income of small kiosks in Tataaran II Village, South Tondano District, Minahasa Regency. The research strategy used is quantitative. Analysis with simple regression. The results showed that the presence of minimarkets affected small kiosk income by 0.374 (37.4%), with other factors explaining the remaining 62.6%. The monthly net income of small kiosk traders has decreased. The average net profit per month before the minimarket existed ranged from IDR 1,000,000 to IDR 2,000,000, while the average net profit per month after the minimarket existed ranged from IDR 500,000 to IDR 1,000,000. One of the reasons customers prefer minimarkets to kiosks is the price